The Effect of Risk Management on Financial Performance: the case of Commercial Banks of Ethiopia - Yifer, Gidey; Thadvuai, Dr.Nageswara Rao; James, Dr.Antiha Lourdu (The journal of contemporary issues in business and government, 2021)
Risk management has become an important topic for financial institutions, especially since the business sector of financial services is related to conditions of uncertainty. The turmoil of the financial industry emphasizes the importance of effective risk management procedures. The aim of this paper was therefore to identify the impact of risk management and its impact on bankperformance on the Ethiopian banks performance. Balanced fixed effect panelregression was used for the data of seven commercial banks in the sample covered theperiod from 2004 to 2015. Four risk management variables that affect banksperformance were selected and analysed. The results of panel data regressionanalysis showed that operational risk indicator (CIR) had negativeand statistically significant impact on banks performance. Capital adequacy ratiohad positive and statistically significant impact on banks performance. In addition this, the study analysed by descriptive statistical tools and on hypothesis testing using regression model. This leads the researcher to conclude in the last section that banks with good risk management policies have a lower risk and relatively higher return on asset. Finally, liquidity ratio and cost to income ratio are significant key drivers of performance of commercials banks in Ethiopia. Indeed focusing and reengineering the institutions alongside these indicators could enhance the profitability as well as the performance of commercial banks in Ethiopia.